Ciherang Stunting Corner: A step to reduce the prevalence of stunting - Putra, Rio Mahesa; Sadiyyah, Fitriani Halimatus (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
Stunting is a serious global public health challenge and a major concern in Indonesia. Stunting refers to impaired child growth, primarily caused by nutritional deficiencies during early development. Data from the Ministry of Health of the Republic of Indonesia indicates that the prevalence of stunting in children in 2023 reached 21,6%, highlighting malnutrition in children as an urgent issue. Various approaches have been undertaken to address this problem, including the Ciherang Stunting Corner, which is the focus in the Ciherang Village, West Java. The method used in this study is quantitative, with a survey approach and data collection. This program emphasizes a community-based and holistic approach to stunting prevention. By involving the community in planning and implementing nutritional interventions, the program can provide solutions tailored to local needs while addressing sanitation and environmental aspects. Initial results show increased community awareness of nutrition and participation in child growth monitoring. Furthermore, the Community Service Learning (KKN) approach has helped to raise awareness about nutrition issues and gather crucial data to support stunting prevention efforts. Integrating the Ciherang Stunting Corner model with a significant reduction in stunting rates is a strategic step in addressing this issue in Indonesia, offering hope for a brighter future for the nation's next generation.